Pelatihan Pengelolaan Inovasi Makanan Berbahan Pangan Lokal dalam Peningkatan Pengetahuan Ibu Hamil di Kelurahan Tembilahan Kota: Pelatihan Pengelolaan Inovasi Makanan Berbahan Pangan Lokal dalam Peningkatan Pengetahuan Ibu Hamil di Kelurahan Tembilahan Kota - Ayuningtyas, Fitria; Siti Maimunah; Selasih Putri Isnawati Hadi (J.Abdimas: Community Health, 2024)
Nutritional disorders in pregnant women often include Chronic Energy Deficiency (CED). Anemia and Chronic Energy Deficiency (CED) in pregnant women are the primary causes of hemorrhage and infection, which are major factors in maternal mortality. Moringa leaves are one of the plants that contain many nutrients, their benefits and nutritional value are not yet widely known by the public. The purpose of this activity is to increase the knowledge of pregnant women in creating additional food menus according to local foods available around them, especially Moringa Leaves. The activity will take place on January 10, 2024, in Tembilahan City Subdistrict, targeting 20 pregnant women with CED. The method used is counseling with pretest and posttest activities to assess the pregnant women's knowledge about supplementary feeding for pregnant women, and a demonstration of making a simple recipe using Moringa Leaves, which can be used as additional supplementary feeding for pregnant women. Respondents are then given the opportunity to ask questions about the material presented. The posttest will measure the increase in knowledge and attitudes of the respondents toward the material delivered. Following the posttest, questionnaires, monitoring, and evaluation of the pregnant women will be conducted. The results of the community service activity showed that after the education, the majority of pregnant women had better knowledge. Pregnant women were very enthusiastic about participating in this activity, as it became a platform for consultation on nutritional needs and the use of local food sources like Moringa leaves as supplementary feeding for pregnant women.